2013
DOI: 10.1002/prot.24249
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic model for secondary structure prediction from protein chemical shifts

Abstract: Protein chemical shifts encode detailed structural information that is difficult and computationally costly to describe at a fundamental level. Statistical and machine learning approaches have been used to infer correlations between chemical shifts and secondary structure from experimental chemical shifts. These methods range from simple statistics such as the chemical shift index to complex methods using neural networks. Notwithstanding their higher accuracy, more complex approaches tend to obscure the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…30 This effort has had some success, as there are a number of reports describing the prediction of secondary structure from a protein sequence and an unassigned peak table. 31 However, by and large, greater success in utilization of chemical shift data has been achieved if a PDB structure is available. 32−35 Despite the complex relationship between structure and chemical shift, this NMR parameter is very robust combined metric of structural and chemical environments and is invariant with respect to acquisition strategy or field strength.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…30 This effort has had some success, as there are a number of reports describing the prediction of secondary structure from a protein sequence and an unassigned peak table. 31 However, by and large, greater success in utilization of chemical shift data has been achieved if a PDB structure is available. 32−35 Despite the complex relationship between structure and chemical shift, this NMR parameter is very robust combined metric of structural and chemical environments and is invariant with respect to acquisition strategy or field strength.…”
Section: Resultsmentioning
confidence: 96%
“…Much ink has been spilled in attempts to interpret or predict structural details that cause a given atom to resonate at a particular frequency . This effort has had some success, as there are a number of reports describing the prediction of secondary structure from a protein sequence and an unassigned peak table . However, by and large, greater success in utilization of chemical shift data has been achieved if a PDB structure is available. …”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, some researchers have utilized chemical shift for the determination of biomolecular structures (Case, 1998;Wishart and Case, 2001). Moreover, some works have studied on protein structure prediction (Cavalli et al, 2007;Lin et al, 2012;Mao et al, 2013;Mechelke and Habeck, 2013;Mielke and Krishnan, 2003;Pastore and Saudek, 1990;Wang, 2004;Zhang et al, 2003) and protein backbone and side chain torsion angle prediction (Shen and Bax, 2013) by using chemical shifts, these results showed that chemical shift is a powerful parameter for the determination of protein structure information.…”
Section: Introductionmentioning
confidence: 95%
“…This suggests an increase of β-sheet and α-helix content upon lipase immobilization of 2.74 and 0.84 percentage points, respectively (Table 1). The existence of hydrogen bonds within secondary structure elements such as β-sheet and α-helix generally helps to maintain protein structure [42,43], which may be one of the reasons why the immobilized lipase exhibited enhanced stability and improved tolerance to organic solvents and ionic liquid [44].…”
Section: Characteristics Of Free Anl and Anl@pd-mnpsmentioning
confidence: 99%